La producción de maracuyá (passiflora edulis) en Colombia: perspectivas para la conservación del hábitat a través del servicio de polinización - Calle, Z.; Guariguata, Manuel R.; Giraldo, E.; Chará, J. (2010)
At a global scale the area devoted to agricultural cultivation that depends upon insect pollination has grown steadily and, therefore, an increased demand of this service would be expected. However, lack of pollinators is not always an essential factor in the productive system at farm level. The present work evaluates the perceptions of passion fruit (Passiflora edulis) producers about the main factors determining their productivity in three Colombian departments (Huila, Meta and Valle del Cauca). In Valle, pollination is manually applied to complement insect pollination, and cultivation areas are more isolated from natural or semi-natural forests, have a higher density and are subjected to more frequent pesticide application than in Huila and Meta. In Meta, cultivation depends exclusively on bee (Xylocopa) pollination, density of cultivated lots is lower, plots are more isolated from natural/semi-natural habitat, and pesticide are applied with a lower frequency. Eventual interventions to insure the provision of natural pollination services would differ. For instance, in Valle and Huila the probability that producers will adopt the concept of pollination services to justify habitat conservation is low, given the intensification level observed. In order to improve the level of natural pollination services supplied for passion fruit culture in these localities, organic production schemes must be promoted, and/or small habitat fringes close to the cultivation areas be restored